Analysis of The Effect of Insufficient Community Engagement in Land Registration Through The Lens of Sunaryati Hartono's Typology of Legal Culture - Tustasari, Rensa Dwi; Musataklima, Musataklima (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2024)
Abstract: This research discusses the factors that cause low community participation in land registration in Sukoanyar Village and the impacts caused, as well as efforts made by the village government to improve land registration. We employ a juridical sociological research method, examining actual community situations to gather necessary facts and data. The findings demonstrated that Sukoanyar Village's low land registration phenomenon remains rooted in a pre-conventional legal culture. This is evident in the community's local customs, which include the conviction that they possess physical control over their land, negating the need for a certificate, their egocentric interests, and their disinterest in government land registration initiatives. The low interest of the community in registering land has several impacts on the certainty of their land rights, including uncertainty of ownership, proneness to disputes, and limited utilization of land ownership rights. In response to this phenomenon, the Sukoanyar Village government made several efforts to improve land registration in the village, including (a) conducting extension and socialization activities involving all villagers to increase public understanding of the importance of land certification and (b) participating in the Complete Systematic Land Registration (PTSL) program conducted by the government through ATR/BPN. Keywords: Community Participation, Land Registration, Legal Culture, Land Certificate.